Optimal control strategy on hybrid energy storage systems to improve system inertia for a bipolar DC microgrid - Yuechao Ma; Guangchen Liu; Hongbin Hu; Jun Tao; Yu Xu (International Journal of Electrical Power & Energy Systems, 2025)
For an islanded bipolar DC microgrid with positive and negative hybrid energy storage systems (HESSs), researchers need to take into account a special problem related to improving the system inertia by the HESSs. To solve this issue, an optimization control strategy for multiple HESSs is proposed. The strategy includes a battery and a supercapacitor (SC) for each HESS, with inertia improvement for the SCs. Specifically, to effectively improve the system inertia, a dynamic power distribution strategy is proposed for solving the unreasonable power distribution problem on positive and negative SCs caused by the asymmetric load power on the positive and negative systems. Subsequently, to improve the system inertia at the right time, 2 operating-state discriminators, one working as an output discriminator and the other as a recovery discriminator, are introduced for each SC. These discriminators are employed for avoiding the influence of SCs on the state-of-charge balancing on the positive and negative batteries and to control the output and recovery actions of the SCs. Based on the 2 operating-state discriminators, 2 virtual DC generators (VDCGs) are introduced into the output paths of the SCs for improving the positive and negative system inertia when the output signals of the operating-state discriminators are activated. Furthermore, to improve the entire system inertia in a bipolar DC microgrid and solve the paradox between the inertia improvement and the lag in the dynamic response speed, a particle swarm algorithm is adopted to joint optimize the parameters of the 2 VDCGs. Finally, to make the SCs output power and improve system inertia repeatedly, 2 time-varying virtual inductors are introduced into the recovery paths of the SCs for accelerating the recovery speed of terminal voltages for SCs when the recovery signals of the operating-state discriminators are activated. The simulation results in different working conditions reveal that the proposed control strategy helps in obtaining reasonable output powers of the positive and negative HESSs, improving the system inertia, ensuring the reliable operation of the SCs, and achieving the optimal operation of the system. Therefore, the accuracy and effectiveness of the proposed control strategy were verified.